2021
DOI: 10.1002/ehf2.13531
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of Takotsubo cardiomyopathy: a systematic review

Abstract: Takotsubo cardiomyopathy (TCM), characterized by reversible ventricular dysfunction, has similar mortality to acute coronary syndrome. With the growing interest in the diagnosis of and interventions for TCM, many risk factors had been found to affect the prognosis of TCM patients, such as age, sex, and pre-existing diseases. Because of the incomplete understanding of the pathophysiologic mechanism in TCM, evidence-based medical therapy for this condition is lacking. Early intervention on risk factors may impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 145 publications
(470 reference statements)
2
15
0
1
Order By: Relevance
“…Patients with lower hematocrit levels tend to be anemia. Some evidence supported the relationship of anemia with poor outcomes of TTS 31,32 . Some analyses applied hematocrit to predict in-hospital death in patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with lower hematocrit levels tend to be anemia. Some evidence supported the relationship of anemia with poor outcomes of TTS 31,32 . Some analyses applied hematocrit to predict in-hospital death in patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Pelliccia et al reported that cardiovascular comorbidities could predispose to stress cardiomyopathy, with the most important being dyslipidemia, obesity, and hypertension [ 16 ]. Another recent article revealed that male gender is associated with worse outcomes [ 17 ]. No other specific risk factors, like chronic heart failure or valvulopathies, were identified [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another recent article revealed that male gender is associated with worse outcomes [ 17 ]. No other specific risk factors, like chronic heart failure or valvulopathies, were identified [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Что касается иАПФ/БРА, ББ, то в настоящее время данные по эффективности этих препаратов в отдаленном периоде заболевания у больных с КТ довольно противоречивы [40,53]. В одном из крупнейших регистров пациентов с КТ продемонстрировали, что использование иАПФ/БРА связано с улучшением выживаемости через 1 год, однако не было получено никаких доказательств улучшения выживаемости при использовании ББ [1].…”
Section: осложнения кт в острый период и их лечениеunclassified